Endogenous nitrogen oxides and bronchodilator S-nitrosothiols in human airways. - Gaston, B (1993)
Recent discoveries suggesting essential bioactivities of nitric oxide (NO.) in the lung are difficult to reconcile with the established pulmonary cytotoxicity of this common air pollutant. These conflicting observations suggest that metabolic intermediaries may exist in the lung to modulate the bioactivity and toxicity of NO.. We report that S-nitrosothiols (RS-NO), predominantly the adduct with glutathione, are present at nano- to micromolar concentrations in the airways of normal subjects and that their levels vary in different human pathophysiologic states. These endogenous RS-NO are long-lived, potent relaxants of human airways under physiological O2 concentrations. Moreover, RS-NO form in high concentrations upon administration of NO. gas. Nitrite (10-20 microM) is found in airway lining fluid in concentrations linearly proportional to leukocyte counts, suggestive of local NO. metabolism. NO. itself was not detected either free in solution or in complexes with transition metals. These observations may provide insight into the means by which NO. is packaged in biological systems to preserve its bioactivity and limit its potential O2-dependent toxicity and suggest an important role for NO. in regulation of airway luminal homeostasis.